Knowledge, Attitude and Practice regarding Influenza A (H1N1) among senior secondary school students of Kanpur city in north India - Nath, Bhola; Midha, Tanu; Kumari, Ranjeeta; Gupta, Sanjay (Indian Journal of Community Health, 2014)
Background: Knowledge regarding Influenza A (H1N1) and its transmission and measures of prevention and control are important for individual protection as well as to contain the spread of the disease. Objective: To study the knowledge, attitude and practice regarding Influenza A (H1N1) among senior secondary school students of Kanpur. Study Design: A cross-sectional, questionnaire-based study. Material and Methods: This study was conducted among students of Class XI and XII of a leading private school in Kanpur. All the students present in the class at the time of the survey were included in the study. Results: Of the 483 students included in the study, 208 (43.1%) knew that it was a viral disease. Of all the students, 303 (62.7%) knew about the mode of transmission. Around 336 (69.6%) of the students knew that fever >38°C was a major symptom. Less commonly occurring symptoms such as diarrhoea (20.9%) and vomiting (14.3%) were known to few students. Conclusion: Knowledge regarding Influenza A (H1N1) needs to be enhanced among senior secondary school students through appropriate awareness programs.